2010
DOI: 10.1055/s-0030-1254080
|View full text |Cite
|
Sign up to set email alerts
|

Einflüsse der medizinischen stationären Rehabilitation auf den Selbstwert und die Selbstwirksamkeit von chronisch kranken Jugendlichen

Abstract: Therapy of chronically ill adolescents in medical rehabilitation affects their self-esteem positively, with differences in self-esteem found between adolescents who show clinically relevant psychological symptoms and those who do not. Only minor changes are however noticed in ratings of self-efficacy at school and other social contexts. Gender- and diagnosis-related differences have not been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
1
0
3
Order By: Relevance
“… 11 There is also evidence that inpatient rehabilitation may improve self-esteem. 12 , 13 There is some evidence that self-esteem also plays a role in the well-being of persons with spinal cord injury (SCI). A 2012 systematic review of psychological resources in persons with SCI showed positive associations between self-esteem and well-being, mental health, community participation, mastery, hope and more effective coping.…”
Section: Introductionmentioning
confidence: 99%
“… 11 There is also evidence that inpatient rehabilitation may improve self-esteem. 12 , 13 There is some evidence that self-esteem also plays a role in the well-being of persons with spinal cord injury (SCI). A 2012 systematic review of psychological resources in persons with SCI showed positive associations between self-esteem and well-being, mental health, community participation, mastery, hope and more effective coping.…”
Section: Introductionmentioning
confidence: 99%
“…Im Weiteren deuten die Ergebnisse darauf hin, dass das Gruppentraining auch Raum für selbsthilfeähnliche Gruppenprozesse zu geben scheint, welche die Akzeptanz eines behinderten Kindes för-dert, den Selbstwert stabilisiert und die Selbstwirksamkeitserwartungen unterstützt; vielfach wird erst damit eine Rehabilitation möglich. Entsprechende Zusammenhänge zwischen der Entwicklung eines spezifischen Selbstwerts (einer hohen Selbstwirksamkeit) für den Erfolg einer stationären Rehamaßnahme wurden kürzlich für körperlich chronisch kranke Jugendliche beschrieben [5,12].…”
Section: Introductionunclassified
“…Ob und inwieweit soziale Ungleichheiten in der stationären Kinderrehabilitation wirken, ist bislang unklar. Die Forschungsschwerpunkte in diesem Versorgungsbereich lagen primär in der Qualitätssicherung und Strukturevaluation rehabilitativer Maßnahmen sowie in deren Wirkung und Nachhaltigkeit [53][54][55][56][57][58][59].…”
unclassified